2016
DOI: 10.1103/physrevc.93.061602
|View full text |Cite
|
Sign up to set email alerts
|

Probing transfer to unbound states of the ejectile with weakly boundLi7onNb93

Abstract: The two-step process of transfer followed by breakup is explored by measuring a rather complete set of exclusive data for reaction channels populating states in the ejectile continua of the 7 Li+ 93 Nb system at energies close to the Coulomb barrier. The cross sections for α + α events from one proton pickup were found to be smaller than those for α + d events from one neutron stripping and α + t events from direct breakup of 7 Li. Coupled channels Born approximation and continuum discretized coupled channels … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 37 publications
0
52
0
Order By: Relevance
“…In the studies with 6 Li on 209 Bi [34] and 159 Tb [35], it is pointed out that the d-ICF cross-sections are much more dominant compared with the transfer cross-sections in inclusive alpha measurements. In recent complete study on transfer induced breakup with 7 Li on 89 Y [36], it is concluded that the transfer induced breakup and noncapture breakup added together can only account for 8 % of inclusive alpha cross-section.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies with 6 Li on 209 Bi [34] and 159 Tb [35], it is pointed out that the d-ICF cross-sections are much more dominant compared with the transfer cross-sections in inclusive alpha measurements. In recent complete study on transfer induced breakup with 7 Li on 89 Y [36], it is concluded that the transfer induced breakup and noncapture breakup added together can only account for 8 % of inclusive alpha cross-section.…”
Section: Resultsmentioning
confidence: 99%
“…The accurate knowledge of these parameters are found to be important for the estimation of the accurate response of the detection setup, which is responsible for the proper angular distribution measurements and consequently extraction of the absolute cross sections of the different reaction processes. The extracted cross sections of various breakup processes for 7 Li+ 93 Nb system using the methods discussed in the present paper were published in our earlier paper [9]. The interpretation of the various observables from coincidence measurements has also been presented.…”
Section: Summary and Applicationsmentioning
confidence: 94%
“…Given a well established 2α-cluster structure of the unbound 8 Be nucleus, the 8 Be+ 8 Be interaction potential poses a four-body problem which is a challenge for the determination of the 8 Be+ 8 Be optical potential (OP) that cannot be deduced from a standard optical model (OM) analysis because of the lack of the elastic 8 Be+ 8 Be scattering data. The knowledge about the α+ 8 Be and 8 Be-nucleus OP's should be also important for the studies of those direct reaction processes that produce 8 Be fragments in the exit channel [5][6][7]. Although the α-nucleus and nucleus-nucleus OP's are proven to be well described by the doublefolding model (DFM) using the accurate ground-state densities of the colliding nuclei and a realistic density dependent nucleon-nucleon (NN) interaction (see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent version of the CDCC theory, the continuum of deuteron is approximated by the square-integrable functions corresponding to positive energies. As a result, this approach can be well extended to study elastic scattering of exotic nuclei that have rather low breakup energies (typical examples are 6 He and 11 Be).…”
Section: Introductionmentioning
confidence: 99%